Refinement of Container Type and Potting Medium Mixture for Production of Quality Seedlings in Chilgoza Pine (Pinus Gerardiana Wall.) - Malik, A. R.; Shamet, G. S. (Indian Forester, 2009)
Pinus gerardiana Wall. (Chilgoza pine) is an important species of dry temperate zone of North-West Himalaya valued chiefly for its edible nuts. Study was conducted to determine the effect of container types viz. root trainer 275 cc (k1), root trainer 300 cc (k2), bottom hole polybabgs (BHP) - 23 x10cm ((k3), and bottom hole polybabgs (BHP) - 16 x10cm ((k4), and growing medium chilgoza forest soil (CFS) (M1), CFS+Sand+moss - 1:1:1 (M2) and CFS+Sand+moss+FYM - 1:1:1:1 (M3) on seedling growth parameters under nursery. Use of BHP - 23Ã—10 cm filled with CFS+sand+mass+FYM proved best for most of the seedling growth parameters under nurseryy condition.